Conflict between human and wild Sumatran Elephant (Elephas maximus sumatranus Temminck, 1847) in Aceh Province, Indonesia - INDIRA NURUL QOMARIAH; TUTIA RAHMI; ZURAIDAH SAID; ARIEF WIJAYA (Society for Indonesian Biodiversity, 2019)
Qomariah IN, Rahmi T, Said Z, Wijaya A. 2019. Conflict between human and wild Sumatran Elephant (Elephas maximus sumatranus Temminck, 1847) in Aceh Province, Indonesia. Biodiversitas 20: 77-84. Aceh Province has the largest habitat for Sumatran elephant. However, the elephant population in the province keeps decreasing due to frequent conflict with humans. This study aimed to observe the trend and pattern of Human-elephant Conflict (HEC) in Aceh, as well as the main causes driving the conflict. To collect information, we carried out desk study, secondary data collection, and interviews with relevant actors in Aceh Jaya, Pidie, and Aceh Timur District. We collected data of HEC during the 2012-2017 period in 16 districts across Aceh. The result shows that during the six years, there were 262 HEC cases occurred in Aceh, where Aceh Timur and Aceh Jaya contributed the highest number of HEC incidence, with 47 and 44 cases respectively. Maximum Entropy analysis shows that the main factor causing the conflict is “Distance from the human settlement” with 84.7% contribution, followed by “Primary forest loss” (14.1% contribution). From the findings, we suggest reforestation in areas that becomes elephant home range and creation of barriers within the conservation forest boundaries. Moreover, HEC mitigation action should also be incorporated in provincial spatial planning (Rencana Tata Ruang Wilayah - Provinsi) to minimize further economic loss and wildlife extinction.